2007
DOI: 10.1177/0021955x07079591
|View full text |Cite
|
Sign up to set email alerts
|

Autoclave Foaming of Poly(ε-Caprolactone) Using Carbon Dioxide: Impact of Crystallization on Cell Structure

Abstract: READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE. https://nrc-publications.canada.ca/eng/copyright Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 26 publications
(35 reference statements)
1
44
0
Order By: Relevance
“…[11,17,18] Making this process suitable for the incorporation of heat labile molecules within the scaffold before the foaming process may represent a great challenge in TE; [7,9] in this work we focused on the solid-state foaming of PCL and PCL-HA nanocomposite and performed the entire process at 37 8C.…”
Section: Resultsmentioning
confidence: 99%
“…[11,17,18] Making this process suitable for the incorporation of heat labile molecules within the scaffold before the foaming process may represent a great challenge in TE; [7,9] in this work we focused on the solid-state foaming of PCL and PCL-HA nanocomposite and performed the entire process at 37 8C.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the presence of the crystal structure means the amount of CO 2 available for bubble growth decreased and the CO 2 concentration in the polymer blend remained higher. As a consequence, the dissolved CO 2 was used for cell nucleation and cell density increased . In blends with higher PLA contents, crystallinity is lower and the polymer receives more blowing agent during saturation because of a greater proportion of amorphous regions .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above analyses, the selected four PCL samples show varied thermal and rheological properties, which may be a favorable aspect for the morphological optimization of PCL scaffolds by providing rich choices. Previous studies have shown that for PCL, foaming at melt state, mild pressure and rapid depressurization are beneficial to acquire a favorable interconnected and macroporous structure [22][23][24][25]27]. Lian, Z. et al has reported that the −dTm/dP of PCL-CO 2 system within 10 MPa is 2.02 • C/MPa, according to the Clapeyron equation [40].…”
Section: Porous Morphology Of Pcl Scaffoldsmentioning
confidence: 99%
“…With the increase of foaming temperature, the foaming process shifts from a solid-state to a melt-state, which generally results in a relatively larger pore size and higher porosity of PCL foams [22]. However, excessive high foaming temperature can also lead to a visible collapse and dense phase of scaffolds [22][23][24][25]. Meanwhile, it has been reported that PCL foams tend to generate favorable macropores when processed under low foaming pressure [23,24,26].…”
Section: Introductionmentioning
confidence: 99%